ASSESSMENT OF RESOURCE POTENTIAL IN THE IMPLEMENTATION OF THE ENTERPRISE STRATEGY: OPPORTUNITIES AND PROBLEMS: https://doi.org/10.5281/zenodo.15407731 - Khudoyberdiyev , Dilmurod (Journal of Contemporary World Studies, 2025)
The article focuses on analyzing the importance of assessing resource potential in implementing enterprise strategy, identifying opportunities and challenges in this process, and proposing practical solutions for enterprises in Uzbekistan. The research objectives include: exploring the theoretical foundations of resource potential, reviewing practical assessment methods, analyzing the state of resource potential in Uzbekistan's enterprises, and evaluating the possibilities of applying advanced international practices, particularly the corporate governance principles of the Organisation for Economic Co-operation and Development (OECD). The study employs a methodology based on an analytical approach, a review of foreign and local literature, and the analysis of practical examples. This research contributes to improving strategic management and the efficient use of resource potential in Uzbekistan's enterprises.